#### Answer

False

#### Work Step by Step

Consider the following counter-example:
Let $f(x) = x^{2}$
Given $s = 2$ and $t = -2$
See that $f(s) = f(2) = (2)^{2} = 4$ and $f(t) = f(-2) = (-2)^{2} = 4$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

False

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.